(untitled) (Communication & Society, 2018)
As key institutions in Western democracies, parliaments have gained importance regarding foreign affairs issues in recent years. Their increasing role as moral tribunes and discussion forums on conflict prevention and resolution have led to the parliamentarization of international affairs. The examination of the parliamentary agenda and the actors who shape it constitutes a fundamental part of agenda-setting studies as applied to the media and political systems. Among these actors, mass media must be highlighted, taking into account the complex process of information gathering for members of Parliament, particularly in cases related to international violent conflicts. Moreover, in the specific situation of the Syrian Civil War, social media have become increasingly important due to the difficulties faced by traditional media in performing their job on the ground. In order to know the impact and roles played by social media in parliamentary debates, we applied a computer assisted quantitative content analysis to 3,249 minutes from the parliaments of United Kingdom, Germany, France, Spain and the EU, as well as a qualitative analysis. The results show that, during the first part of the conflict, social media were regarded by European parliaments as positive tools for the dissemination of information whereas, in the second phase, the diffusion of jihadist propaganda by such media completely altered the attitudes toward them.